The Environmental Changes And The Adoption Of New Strategies In The International Organizations: A Study On The Islamic Development Bank - M. Adwan, Basela Majed (2008)

(untitled)
In 1975 the Islamic Development Bank was established in Jeddah-Kingdom of Saudi Arabia in order to foster economic development and social progress of the member countries and the Muslim communities in non-member countries in accordance with the principles of the Islamic Shariah.